FACTORS THAT INFLUENCE CUSTOMER LOYALTY IN USING E-COMMERCE - Abdul Kadir Othman; Lailatul Faizah Abu Hassan; Muhammad Anuar Mohd Ibrahim; Nur Sazatul Anira Sapuan; Muhammad Sofiq Saripin; Zaidatul Nadhirah Roslan (Journal of Islamic Management Studies, 2020)
Electronic commerce or E-commerce is a platform where a process of purchasing goods or services can be done through an online medium. The emerging trend and development of Information Technology (IT) and the increasing use of Internet in today’s society has brought E-commerce to another level. The reason for this is that service providers have realized that building long-term relationships with customers provides a way to reduce their defection rates, reducing costs and increasing revenues. The success of a relationship partly depends on the level of trust that exists between the customer and the provider of the product / service. Consumers start to put interest in using e-commerce provided in today’s market. Consumer loyalty is the greatest achievement for a company that aims to be a leader or to have longevity in the market. Thus, this study was conducted to investigate the factors that influence customer loyalty in using e-commerce services. Analysing 119 data collected from e-commerce consumers, the results of regression analysis indicate that trustworthiness, web design, word of mouth and switching cost contribute to customer loyalty. The recommendations are discussed in detail in the paper.